Cooperative Partnerships for environmental conservation in the rural sector through the interaction community- firm and research center (Revista LIDER, 2020)
This study is based on the results of partnership between academia, industry, non-governmental organization and rural communities Zapotillo Canton province of Loja in Ecuador. Specifically focuses socioeconomic and environmental impacts that had on the Human Development Index, also showing with evidence chow this experience is part of the sustainable rural development contributing to the conservation of the dry forest ecosystem through the use and sustainable use of the fruit of Palo Santo (Bursera graveolens), improving the quality of life of the peasants, generating corporate profits and university extension.